1999
DOI: 10.1111/j.1574-6976.1999.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease P: the diversity of a ubiquitous RNA processing enzyme

Abstract: Ribonuclease P is the endonuclease required for generating the mature tRNA 5'-end. The ribonucleoprotein character of this enzyme has now been proven in most organisms and organelles. Exceptions, however, are still the chloroplasts, plant nuclei and animal mitochondria where no associated RNAs have been detected to date. In contrast to the known RNA subunits, which are fairly well-conserved in size and structure among diverse phylogenetic groups, the protein contribution to the holoenzyme is highly variable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…Extensive purification analysis of RNase P from HeLa cells has revealed that the nuclear form of this tRNA processing holoenzyme is composed of at least 10 protein subunits associated with a single RNA species, H1 RNA (Table 1; Eder et al+, 1997;)+ These protein subunits are designated Rpp14, Rpp20, Rpp21, Rpp25, Rpp29, Rpp30, Rpp38, Rpp40, hPop5, and hPop1 (Lygerou et al+, 1996b;Eder et al+, 1997;Jarrous et al+, 1998Jarrous et al+, , 1999avan Eenennaam et al+, 1999van Eenennaam et al+, , 2001)+ The tight association of these proteins with highly purified nuclear RNase P obtained by different purification schemes implies that they constitute the core structure of the holoenzyme )+ A recent study has shown that the mitochondrial form of HeLa RNase P possesses an RNA that is identical to the H1 RNA (Puranam & Attardi, 2001)+ This enzyme has a sedimentation coefficient of ;17S in glycerol gradients, compared to ;15S of the nuclear counterpart, and exhibits properties typical of a ribonucleoprotein enzyme (Puranam & Attardi, 2001)+ This finding contradicts earlier biochemical analyses that support the concept that human mitochondrial RNase P is not a ribonucleoprotein complex (Rossmanith et al+, 1995;Rossmanith & Karwan, 1998)+ These opposing findings provoke further debate on the biochemical nature of mitochondrial and other organellar RNase P enzymes (Frank & Pace, 1998;Schon, 1999;Altman et al+, 2000;Gegenheimer, 2000;Salavati et al+, 2001), and therefore more biochemical and genetic means should be applied to resolve this issue+ Nuclear RNase P purified from Saccharomyces cerevisiae has nine distinct protein subunits and genetic studies established that these subunits are essential for yeast viability and enzyme activity in tRNA processing (see Xiao et al+, 2001)+ A multi-subunit ribonucleoprotein has also been described for nuclear RNase P purified from Aspergillus nidulans (Han et al+, 1998)+ In addition to the protein subunits described above (Table 1), several other proteins transiently interact with RNase P in yeast and human cells+ As judged by twohybrid genetic screens in yeast, the subunit Rpp20 interacts with the heat shock protein Hsp27 and the subunit Rpp14 contacts several proteins, including the LIM domain protein 1 (LIMD1) and HSPC232 ; the latter is an SR-rich protein that exhibits partial similarity to splicing factors SC-35 and SRp46+ The interaction of Rpp20 with Hsp27 was verified by biochemical analysis )+ In S. cerevisiae, a complex of seven Sm-like proteins (Lsm2-8) is associated with the precursor RNA subunit, Rpr1, of nuclear RNase ...…”
Section: Ribonucleoprotein Complexes Of Rnase Pmentioning
confidence: 97%
“…Extensive purification analysis of RNase P from HeLa cells has revealed that the nuclear form of this tRNA processing holoenzyme is composed of at least 10 protein subunits associated with a single RNA species, H1 RNA (Table 1; Eder et al+, 1997;)+ These protein subunits are designated Rpp14, Rpp20, Rpp21, Rpp25, Rpp29, Rpp30, Rpp38, Rpp40, hPop5, and hPop1 (Lygerou et al+, 1996b;Eder et al+, 1997;Jarrous et al+, 1998Jarrous et al+, , 1999avan Eenennaam et al+, 1999van Eenennaam et al+, , 2001)+ The tight association of these proteins with highly purified nuclear RNase P obtained by different purification schemes implies that they constitute the core structure of the holoenzyme )+ A recent study has shown that the mitochondrial form of HeLa RNase P possesses an RNA that is identical to the H1 RNA (Puranam & Attardi, 2001)+ This enzyme has a sedimentation coefficient of ;17S in glycerol gradients, compared to ;15S of the nuclear counterpart, and exhibits properties typical of a ribonucleoprotein enzyme (Puranam & Attardi, 2001)+ This finding contradicts earlier biochemical analyses that support the concept that human mitochondrial RNase P is not a ribonucleoprotein complex (Rossmanith et al+, 1995;Rossmanith & Karwan, 1998)+ These opposing findings provoke further debate on the biochemical nature of mitochondrial and other organellar RNase P enzymes (Frank & Pace, 1998;Schon, 1999;Altman et al+, 2000;Gegenheimer, 2000;Salavati et al+, 2001), and therefore more biochemical and genetic means should be applied to resolve this issue+ Nuclear RNase P purified from Saccharomyces cerevisiae has nine distinct protein subunits and genetic studies established that these subunits are essential for yeast viability and enzyme activity in tRNA processing (see Xiao et al+, 2001)+ A multi-subunit ribonucleoprotein has also been described for nuclear RNase P purified from Aspergillus nidulans (Han et al+, 1998)+ In addition to the protein subunits described above (Table 1), several other proteins transiently interact with RNase P in yeast and human cells+ As judged by twohybrid genetic screens in yeast, the subunit Rpp20 interacts with the heat shock protein Hsp27 and the subunit Rpp14 contacts several proteins, including the LIM domain protein 1 (LIMD1) and HSPC232 ; the latter is an SR-rich protein that exhibits partial similarity to splicing factors SC-35 and SRp46+ The interaction of Rpp20 with Hsp27 was verified by biochemical analysis )+ In S. cerevisiae, a complex of seven Sm-like proteins (Lsm2-8) is associated with the precursor RNA subunit, Rpr1, of nuclear RNase ...…”
Section: Ribonucleoprotein Complexes Of Rnase Pmentioning
confidence: 97%
“…Bacterial RNase P (RNA) differs from other ribozymes, such as the self-splicing group I introns, in its natural trans-cleavage activity and its biologically important capacity to recognize a large variety of ptRNAs, even including non-tRNA substrates in some organisms (reviewed in Ref. 3). The enzyme has to act with similar efficiency on ptRNAs carrying unrelated 5Ј-flanking sequences and which differ in structural details of their mature domains.…”
Section: ј-Deoxy and 2ј-fluorinementioning
confidence: 99%
“…Endonucleolytic 5Ј maturation of tRNA primary transcripts is catalyzed by the ribonucleoprotein enzyme ribonuclease P (RNase P) 1 in all three domains of life (Archaea, Bacteria, and Eukarya) as well as in mitochondria and chloroplasts (1)(2)(3). Bacterial RNase P enzymes are composed of a catalytic RNA subunit (4), ϳ400 nucleotides (nt) in length, and a single small protein of typically 120 amino acids (5).…”
mentioning
confidence: 99%
“…Ribonuclease P (RNase P) is an essential ribonucleoprotein enzyme responsible for the 59-end maturation of tRNAs (Altman and Kirsebom 1999;Schön 1999;Hartmann and Hartmann 2003;Evans et al 2006). The bacterial RNase P holoenzyme consists of an RNA subunit of z380 nucleotides (nt) and a small basic protein (z13 kDa), and in vitro, RNA subunits of bacterial RNase P enzymes are catalytically active in the absence of the protein subunit (Guerrier-Takada et al 1983).…”
Section: Introductionmentioning
confidence: 99%